The opinions of medicine faculty students regarding cheating in relation to Kohlberg's moral development concept - Semerci, Ç (Soc Personality Res Inc, 2006)
In all education systems, cheating is a serious problem. It is regarded as a significant problem because of its frequency and interference in learning and evaluation processes. As cheating is not a fair behavior, it can be dealt with morally. Kohlberg (1969, 1979, 1984) tried to explain our moral behaviors by relating moral development to age and intellectual development. The relationship between Kohlberg's moral development concept and cheating could help find the reasons and solutions for cheating. The aim in this paper is to explain the opinions of the students attending the Faculty of Medicine at Firat University in Turkey related to cheating in terms of Kohlberg's moral development. A survey method was used in the form of a questionnaire containing of 15 questions. It revealed that in Turkey, at Firat University, Medicine Faculty students emphasize that cheating is unlawful or a sin and forgery; however, they themselves cheat during examinations.
Keywords: medicine faculty; cheating; Kohlberg's moral development; attitude; examination